2017
DOI: 10.4049/jimmunol.1600108
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α Negatively Regulates the Expression of Endothelial Nitric Oxide Synthase and Nitric Oxide Production: Implications for Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a known risk factor for endothelial dysfunction. Murine and human lupus studies have implicated a role for IFNα in vascular abnormalities associated with impaired blood vessel dilation. However, the impact of IFNα on mediators that induce vasodilation and modulate inflammation including endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) bioavailability are unknown. The objectives of this study were to determine how IFNα promotes endothelial dysfunction in SLE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 39 publications
2
40
0
1
Order By: Relevance
“…As expected, we observed that VEGF caused an enhancement in NO production in HUVECs. However, endothelial production of NO was reduced by IFN treatment, which is in agreement with a very recent report that IFN-α inhibits NO production in HUVECs [43]. Vascular homeostasis is achieved through the finetuned regulation of the integrity of the endothelial cell monolayer by vasoactive modulators, and a proper amount of NO is essential for correct endothelial functioning.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, we observed that VEGF caused an enhancement in NO production in HUVECs. However, endothelial production of NO was reduced by IFN treatment, which is in agreement with a very recent report that IFN-α inhibits NO production in HUVECs [43]. Vascular homeostasis is achieved through the finetuned regulation of the integrity of the endothelial cell monolayer by vasoactive modulators, and a proper amount of NO is essential for correct endothelial functioning.…”
Section: Discussionsupporting
confidence: 90%
“…The type I IFNs also have effects outside the immune system, such as impairment of endothelium-dependent vasorelaxation and endothelial progenitor cell function, which slow down the repair process of damaged endothelium 84–86. Further, IFN-α inhibits eNOS expression and impairs insulin-mediated nitric oxide production in endothelial cells,87 enhances foam cell formation88 and alters platelet function 89. These observations can be linked to the unexpectedly high prevalence of atherosclerosis and cardiovascular disease in patients with SLE 90.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous inflammatory production of interferon-alpha (IFN-α) and subsequent increased expression of IFN-α-regulated genes, referred as IFN signature, due to activation of plasmacytoid dendritic cells by immune complexes, consisting of autoantibodies in combination with deoxyribonucleic acid-(DNA-) or ribonucleic acid-(RNA-) containing autoantigens, have been reported in SLE patients. Studies on animals and humans have provided evidence that IFN accelerate atherosclerosis on multiple stages [149][150][151].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…To date, no studies were conducted to determine direct effects of IFN on eNOS function and NO generation. However, IFN type I has been reported to have impact on enzyme cofactors, its specific transcription factors, and oxidative stress pathways [151]. Animal and human studies indicate that IFN-α leads to depletion of BH 4 via oxidation, serving as a potential mediator of eNOS uncoupling and oxidative stress [152,153].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%